Quality of Services and resource management in multimedia networks - Luo, Tao. (2008)
Multimedia services have complex or even conflicting demands on the management of network resources and the provision of QoS. Our research objectives are to design appropriate mechanisms and algorithms for networks to provide multimedia services with reasonable and efficient quality of service.